ANALISIS RETURN ON EQUITY, CURRENT RATIO DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Khadijah, Tiur Mayda Shyella Hasibuan (LPPM Universitas Putera Batam, 2022)
Stock criteria in the process in the company's system in animating the e-corporate performance system. The more interest in working in the company, the more prospects there are for an increase in the price or value of the stock. Therefore, the company also participates in classifying the performance of companies and employees so that they do not experience a decline in stock prices every year. The choice of a way to indicate that the company's performance is good is to compare the company's financial rationns from thee previious years to thhe followiing year’s. The studing aim to examine for effect a ReturnOn Equiity, Current Ratio and NetProfit Margin on stockprices in pharmaceuticalcompanies listed in a Indonesia StockExchange. 2016-2020 years. The population in this study amounted to 12 pharmaceutical companies with the period 2016-2020. While the sample to be selected by purposive sampling method with a total of 7 companies for 5 years the data processed as many as 35 data. The data were tested using basic assumptions, classical assumption test, multiple linear regression test and hypothesis testing. The results show that Return OnEquity, Current Ratio and Ne ProfitMargin simultaneously has as signficant efect in stocks price, this can’t seens froms thesignificance value’s of the F test of 0.147 > 0.05. Return On Equity has a positive and insignificant effect on stock prices, it can be seen from the significance value 0.143 > 0.05. Current Ratio has a positive and insignificant effect on stock prices, it can be seen from the significance value of 0.210 > 0.05. Net Profit Margin has a positive and insignificant effect on stock prices, it can be seen from the significance value of 0.767 > 0.05.